Automated rubber seed clones identification using QRE1113 and Arduino UNO: article / Fakhry Rasien Alias - Alias, Fakhry Rasien (2014)
This project is about to identify and differentiate types of rubber seed clones. Rubber seed clones differentiator consists of Arduino UNO as a microcontroller and QRE-1113 as a sensor. Reflectance, the proportion of light striking a surface which is reflected off it, produced by rubber seed clones can be verified by these two types of sensor. In this project, there are five types of rubber seed clones used which are RRIM 2002, RRIM 2015, RRIM 2020, RRIM 2023 and RRIM 2024. Since the rubber seeds produce different reflectance intensity at different angle, there are three sensors used in this project to taken the reading from three different angles. There are 30 samples reading was taken from 5 difference clones. The readings from sensor, in voltage form, will be shown on the LCD display. For analysis part, this project goes through the one-way analysis of variance (ANOVA) to measure the mean, median, standard error minimum value and maximum value. The Microsoft Office Excel was used to construct the error plot from the value got at one-way analysis of variance (ANOVA).